Development and characterization of high-protein flakes made from Spirulina platensis in instant cereal drinks enriched with probiotic milk powder - Bintang Efrata Aprilia; Dwi Larasatie Nur Fibri; Endang Sutriswati Rahayu (Food Production, Processing and Nutrition, 2025)
Abstract Children aged 5 to 12 years fail to meet the necessary amount of protein requirements. This condition can lead to microbial imbalances and may interfere with the absorption of nutrients that are not optimized. There is a need for a convenient high-protein snack with probiotics. Therefore, this study developed a high protein instant cereal drink made from Spirulina platensis and probiotics of Lactiplantibacillus plantarum Dad-13. To improve the nutritional value, sorghum flour was added. This study aims to assess the physicochemical and sensory properties of a probiotic cereal drink, as well as the survival of probiotics throughout its shelf life. This study used a non-factorial completely randomized design with three replicates of experiments. The factor of the treatment was the percent ratio of flakes between Spirulina platensis and sorghum flour (1:50, 3:48, and 5:46%). The viability of probiotics was evaluated at three storage temperatures (20, 30, and 37 oC). Based on the results, the ratio of Spirulina platensis and sorghum flour resulted in significantly different levels of preference (overall liking) and physicochemical characterization (p < 0.05). Spirulina 1%:50% sorghum flour is the chosen formula because it is the most preferred. This product has the crispiest texture and the brightest color. It can be a suitable snack for children due to it can be a source of protein (12.56 g/100 g) and fiber (4.68 g/100 g). Lowering the storage temperature may slow the rate of viability loss. This study showed that children like the developed high-protein instant cereal drinks. The viability of the probiotic cells conforms to the standard, indicating the potential to provide health benefits. Graphical Abstract